Health facilities roles in measuring progress of universal health coverage - Muhiuddin Haider; Emily Vooris; Ananya Krishnan (International Journal of Public Health Science (IJPHS), 2021)
Outlined in Sustainable Development Goal 3.8, universal health coverage (UHC) ensures all people can access affordable and equitable essential health services without facing economic challenges. Advised by the World Health Organization (WHO), countries can strengthen their health systems and subsequently UHC by establishing a robust health system on a framework of service delivery; health workforce; information; medical products, vaccines and technologies; financing; and leadership and governance. By achieving UHC, countries progress in other health-related goals and provide for healthier children, a stronger workforce and long-term economic development. As announced by Prime Minister Sheikh Hasina in 2011, Bangladesh has remained committed towards UHC through the implementation of programs that increase availability and financial accessibility of essential health services. To produce information regarding their contribution to UHC and specifically the work of its health facilities, Bangladesh produced the 2017 Bangladesh health facilities survey (BHFS). Based on a qualitative analysis, the 2017 BHFS provides substantial information regarding the presence of essential services within different facilities and locations. However, the survey inadequately addresses other components that contribute to availability and accessibility of services, including utilization, patient load, quality of care and financial burden. Subsequently, the 2017 BHFS does not provide a comprehensive evaluation of their health facilities and their contribution to UHC. Arguably, a future survey must address these topics and incorporate a multidisciplinary approach to successfully implement UHC. This approach would incorporate multidisciplinary stakeholders including economists, public health figures and politicians to address challenges such as financial burden, public distrust, and qualified training of providers.